PENGARUH MODEL KOOPERATIF TIPE SCRAMBLE TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SDN 1 LAMBHEU ACEH BESAR - Dhiya Gebrina; Nurmasyitah; Mislinawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to examine the effect of the Scramble-type cooperative learning model on students’ learning outcomes in Pancasila Education among fourth-grade students at SDN 1 Lambheu Aceh Besar. The research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The population consisted of all fourth-grade students, with the sample comprising an experimental class and a control class selected through purposive sampling. Data were collected using a 20-item multiple-choice test administered as pretest and posttest. The data were analyzed using the N-Gain test, normality and homogeneity tests, and hypothesis testing through an independent sample t-test with the assistance of SPSS. The findings revealed that students taught using the Scramble-type cooperative learning model achieved higher learning outcomes compared to those taught using the direct learning model. The hypothesis testing showed a significance value (2-tailed) < 0.05, indicating that Ha was accepted and Ho was rejected. Therefore, it can be concluded that the Scramble-type cooperative learning model has a significant effect on the learning outcomes of fourth-grade students in Pancasila Education at SDN 1 Lambheu Aceh Besar.